Knowledge, awareness and dietary practice on urolithiasis among general population in Kuantan, Pahang, Malaysia: Preliminary findings (journal) - Sowtali, Siti Noorkhairina; Mohd Arifin, Siti Roshaidai; Nazli, Nor Syawanidamia; Mohd Shukri, Nor Azwani; Khattak, Muhammad Muzaffar Ali Khan; Ab Rashid, Islah Munjih; Muhamad, Suhana; Adzali, Fatin Noraliah (Page Press Publications, 2021)
Background: To date, no studies have been published at evaluating the level of knowledge, awareness and practice of dietary, particularly regarding to urolithiasis in patients or the general population. This study aims to provide basic information on the level of knowledge, awareness and dietary practice among general population in Kuantan, Pahang. Design and Methods: The respondents (n=30) were conveniently recruited within 10 kilometres radius of Kuantan city between January and February 2020. Ethics approval was obtained from Kuantan Municipal Council prior to data collection, and respondents were given adequate time to complete the survey. The data were obtained using semi-guided administered questionnaires, which consists of four parts: socio-demographic data, lifestyle and clinical history (Part A); attitude and awareness on dietary practice regarding urolithiasis (Part B); food frequency questionnaire on urolithiasis (Part C) and level of knowledge on urolithiasis (Part D). The items of the questionnaire were developed based on the authors' expertise, previous literature review, and experience with pre-test in 15 patients with urolithiasis. The content validity index and Cronbach alpha value were calculated for validity and reliability, and the data was analysed descriptively using Statistical Package for Social Sciences version 25. Results: Majority of the respondents were women (70%), Malay (83.3%), mean age of 33.97 (±9.27), married (63.3%), completed higher education level (60%), working with government sector (33.3%) and have fixed monthly income (53.3%). Some of them had hypertension (n=4), diabetes (n=1), gout (n=1) and intestinal problem (n=1). Majority (80%) claimed having no family history of urolithiasis, consumed alcohol (10%), exercise with average frequency 2-3 times/week (46.7%) and heard about urolithiasis from healthcare worker (46.7%). The respondents’ awareness about urolithiasis is considered to be good [81.23 (±9.98)] but having poor knowledge score [2.70 (±1.149)]. Majority preferred wholemeal bread, white rice, chicken meat, mackerel fish, chicken egg, apple, carrot, mustard leave and fresh milk in daily intake. Lesser plain water intake than standard requirement was noticed among respondents. Seasoning powder was commonly used for seasoning. Conclusions: Generally, the general population of Kuantan, Pahang was aware of urolithiasis disease but needed more information on dietary aspect in terms of knowledge and food choice. There will be more awareness campaigns in the future.